FARMERS’ PERCEIVED OUTCOMES FROM PARTICIPATING IN THE RADIO SCHOOL-ON-AIR ON ORGANIC AGRICULTURE - Gabrillo, Christina A; Widjayanthi, Lenny (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
For farmers to learn about new knowledge and practice of organic agriculture, the radio School-on-the- Air (SOA) was used as an extension tool to promote a sustainable farming practice. This paper sought to find out farmers’ perceived outcomes from their participation in the SOA on organic agriculture (OA) in the two provinces of Leyte and Southern Leyte in Eastern Visayas, Philippines. It also identified the crops grown by farmers and determined the effectiveness of the radio SOA as an extension tool. The study employed a survey with randomly selected 125 farmer-graduates of SOA in Leyte and 130 in Southern Leyte. Results revealed that both of the two farmer-groups have: 1) acquired few skills, 2) moderately adopted the OA technology, 3) regarded high impact on its economic significance, and 4) gained high knowledge to benefit their communities and surrounding environment. In Bennett’s hierarchy of program evaluation, the perceived outcomes has reached its highest rank of 7.0. This means that the SOA on organic agriculture has not only made an impact on the farmers themselves but also to the communities in which they live. In totality, the Leyte farmer-group perceived the radio SOA as highly effective and very highly effective for Southern Leyte farmers when it comes to the: 1) content, 2) radio hosts/resource persons, and 3) technical aspects/reception of the program. In the Wilcoxon Rank-Sum test, a significant difference existed between the two farmer-groups of Leyte and Southern Leyte as regards the effectiveness of SOA host/resource persons of organic agriculture with the latter giving a higher evaluation rating.